2020
DOI: 10.1017/cjn.2020.62
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sleep Disorder on Delirium in Post-Cardiac Surgery Patients

Abstract: Background: Post-cardiac surgery patients exhibit a higher incidence of postoperative delirium (PD) compared to non-cardiac surgery patients. Patients with various cardiac diseases suffer from preoperative sleep disorder (SPD) induced by anxiety, depression, breathing disorder, or other factors. Objective: To examine the effect of sleep disorder on delirium in post-cardiac surgery patients. Methods: We prospectively selected 186 patients undergoing selective cardiac val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 52 publications
1
18
2
Order By: Relevance
“…According to the results of a meta-analysis, pre-existing sleep disturbances may be associated with post-operative delirium (POD) ( 63 ). A study about cardiac surgery found that pre-operative sleep disorder was significantly associated with POD and was the main predictor of POD ( 64 ), especially in older individuals ( 65 ). The risk of post-operative delirium is significantly higher in older adults with chronic sleep disturbance before hospitalization than in those without sleep disorders.…”
Section: The Effects Of Perioperative Sleep Disorder On Patients' Post-operative Outcomesmentioning
confidence: 99%
“…According to the results of a meta-analysis, pre-existing sleep disturbances may be associated with post-operative delirium (POD) ( 63 ). A study about cardiac surgery found that pre-operative sleep disorder was significantly associated with POD and was the main predictor of POD ( 64 ), especially in older individuals ( 65 ). The risk of post-operative delirium is significantly higher in older adults with chronic sleep disturbance before hospitalization than in those without sleep disorders.…”
Section: The Effects Of Perioperative Sleep Disorder On Patients' Post-operative Outcomesmentioning
confidence: 99%
“…11,12 A prospective observational study in our center discovered that the incidence of preoperative poor sleep quality in patients with cardiac valve disease was about 57%. 13 Poor sleep quality can predispose individuals to pain conditions, and increasing pain severity further exacerbates their sleep quality. 14,15 There have been reports of an increased risk of postoperative pain sensitivity in patients with preoperative poor sleep quality who have undergone noncardiac surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In one retrospective trial, the control group was matched for age, sex, operated side, type of operation, mode of component fixation, year of operation, surgeon, and type of anesthesia ( 28 ). In seven trials, patients only underwent cardiac surgery ( 33 , 36 39 , 42 , 44 ), in 20 trials, only non-cardiac surgeries ( 17 , 18 , 27 30 , 32 , 34 , 35 , 40 , 41 , 43 , 45 52 ), and in two trials, both cardiac and non-cardiac surgeries ( 16 , 31 ). All the patients in the included RCTs underwent non-cardiac surgeries.…”
Section: Resultsmentioning
confidence: 99%
“…Nine trials focused on patients with sleep-disorder breathing or OSA ( 16 , 28 , 30 , 31 , 34 , 37 , 39 , 41 , 49 ), and the other trials studied patients with several sleep problems. Thirteen trials described the effect of preoperative sleep problems on the incidence of POD ( 16 , 27 , 28 , 30 , 31 , 33 – 35 , 37 , 39 42 ), and the other trials described postoperative sleep quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation